2011
DOI: 10.1016/j.biopsycho.2011.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Gene environment interactions with a novel variable Monoamine Oxidase A transcriptional enhancer are associated with antisocial personality disorder

Abstract: Monoamine Oxidase A (MAOA) is a critical enzyme in the catabolism of monoaminergic neurotransmitters. MAOA transcriptional activity is thought to be regulated by a well characterized 30 base pair (bp) variable nucleotide repeat (VNTR) that lies approximately ~1000 bp upstream of the transcriptional start site (TSS). However, clinical associations between this VNTR genotype and behavioral states have been inconsistent. Herein, we describe a second, 10 base pair VNTR that lies ~1500 bp upstream of the TSS. We pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 37 publications
3
48
0
3
Order By: Relevance
“…Recently, Philibert et al (2011) identified a new polymorphic VNTR in the promoter region of MAOA located 1.5 kb upstream from the start ATG codon and consisting of 10-bp tandem repeats. This VNTR enhances the transcription of MAOA, and its regulatory effect is much more sound than that of the 30 bp-VNTR.…”
Section: Monoamine Oxidases a And Bmentioning
confidence: 99%
“…Recently, Philibert et al (2011) identified a new polymorphic VNTR in the promoter region of MAOA located 1.5 kb upstream from the start ATG codon and consisting of 10-bp tandem repeats. This VNTR enhances the transcription of MAOA, and its regulatory effect is much more sound than that of the 30 bp-VNTR.…”
Section: Monoamine Oxidases a And Bmentioning
confidence: 99%
“…It is known that a reduction of the activity of the platelet MAO-A is related with impulsivity and PD and that it is also associated with 5-HAA in LCR, thus presenting an inverse correlation with rates at scales that search for sensations and impulsivity (Schalling, Asberg, Edman, & Oreland, 1987). In addition, recent studies have replicated of gene x environment (G x E) interactions involving the MAO-A, indicating that activity MAO-A genetic variant who were more associated to PD traits like as hostility and impulsivity (Fergusson, Boden, Horwood, Miller, & Kennedy, 2011;Philibert et al, 2011;Reti et al, 2011) …”
Section: Biomarkers In Personality Disordersmentioning
confidence: 92%
“…An association between low affinity allele mao-a polymorphisms in women with a history of childhood sexual abuse and the later development of alcoholism and antisocial personal disorders has been reported (Ducci et al 2008). A novel 10 bp VNTR *1,500 bp upstream of the transcriptional site has been associated with antisocial personality disorder in female children with a history of child abuse (Philibert et al 2011). In female patients with panic disorder, longer, higher activity mao-a promoter alleles were significantly more frequently found than in control females (Deckert et al 1999).…”
Section: Modulation Of Mao-a Expression In Neuropsychiatric Disordersmentioning
confidence: 97%